A collaboration to develop Chinese supervision capacity: the professional context, the model, and lessons learned. Issue 1 (2nd January 2023) - Goodyear, Rodney K.; Duan, Changming; Falender, Carol; Lin, Xiubin; Jia, Xiaoming; Jiang, Guangrong; Qian, Mingyi
ABSTRACT: To develop a more competent clinical supervision workforce, the Chinese clinical and counseling psychology leadership in 2015 formed a collaboration that included two Chinese professional organizations and three US psychologists. The authors describe the context for this collaboration and the resulting program, which has now trained more than 600 supervisors. We describe ways in which program content and pedagogy continually are being adapted to better ensure relevance to a Chinese audience. We also discuss the collaboration itself, including implications for those who might want to participate in a similar, cross-national collaboration.